Model test study on the effect of dynamic compaction under low water content. - Xiaoshuang Zhang (Public Library of Science (PLoS), 2021)
Dynamic compaction is a cost-effective foundation treatment technology, that is widely used in various types and conditions of foundations. However, due to the limitation of natural conditions (water content between 3% and 8%) in north-western China, it is difficult to meet the requirements of the optimal water content during dynamic compaction. To better treat a foundation with a low water content, a series of model tests were carried out by using homemade test equipment to study the influence of the ramming energy and η value on the efficiency of dynamic compaction under a low water content. The results showed that the improvement of the energy level could compensate for the poor effect of dynamic compaction caused by a low water content in arid regions. Compared with that at the optimal water content, the efficiency of dynamic compaction was 58.1% to 66.2% at a low water content and excited the optimal energy level. Increasing the η value was also beneficial to improving the effect of dynamic compaction. Hence, the optimal energy level combined with the appropriate η value is of great merit in treating the foundation of arid regions by using the dynamic compaction method, which provides new parameter suggestions and engineering guidance for dynamic compaction construction in arid areas.